2003
DOI: 10.1016/s0014-5793(03)00096-6
|View full text |Cite
|
Sign up to set email alerts
|

CD36‐mediated endocytic uptake of advanced glycation end products (AGE) in mouse 3T3‐L1 and human subcutaneous adipocytes

Abstract: Interaction of advanced glycation end products (AGE) with AGE receptors induces several cellular phenomena potentially relating to diabetic complications. We here show that AGE-modi¢ed bovine serum albumin (BSA) is endocytosed by adipocytes via CD36. Upon di¡erentiation, 3T3-L1 and human subcutaneous adipose cells showed marked increases in endocytic uptake and subsequent degradation of [125 I]AGE-BSA, which were inhibited e¡ectively by the anti-CD36 antibody. Ligand speci¢city of CD36 for modi¢ed BSAs was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 36 publications
1
56
1
1
Order By: Relevance
“…Adipocytes express CD36, a scavenger receptor that binds AGEs (incl. CML) and facilitates endocytosis and degradation 21,22 . Thus, fat mass could influence circulating AGE concentrations through a role in the catabolism and breakdown of AGE.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes express CD36, a scavenger receptor that binds AGEs (incl. CML) and facilitates endocytosis and degradation 21,22 . Thus, fat mass could influence circulating AGE concentrations through a role in the catabolism and breakdown of AGE.…”
Section: Discussionmentioning
confidence: 99%
“…125 I-rHuTWEAK was prepared by using an Iodogen coating tube (Pierce) as described (35). Briefly, 200 g of rHuTWEAK was incubated with Na 125 I (0.925 MBq) in 200 l of 0.5 M sodium phosphate buffer (pH 7.4) for 20 min at 37°C, and then dialyzed against PBS.…”
Section: Preparation Of 125 I-rhutweak and Hp-hb Complexesmentioning
confidence: 99%
“…Cellular binding of 125 I-rHuTWEAK was performed in accordance to that of advanced glycated end product-modified BSA by CD36 as described previously (35). For cell binding assay, cells were incubated with 100 ng/ml 125 I-rHuTWEAK at 4°C in RPMI 1640 containing 3% BSA for 3 h. After incubation, cells were washed three times with ice-cold PBS and lysed with 0.1 M NaOH.…”
Section: Cellular Binding Of 125 I-rhutweak By Cd163-cho Cellsmentioning
confidence: 99%
“…We have shown that dietary AGEs acutely impair endothelial function (18,19), an effect counteracted by benfotiamine (20), a transketolase activator that blocks several hyperglycemiainduced pathways, including the formation of AGEs (21). AGEs might interact with adipocytes through AGE receptors (22) and induce cellular dysfunction via generation of reactive oxygen species (23), a pathway probably responsible for the AGE-induced downregulation of leptin secretion in vitro (24).…”
Section: Diethelm Tschoepe MDmentioning
confidence: 99%